2000
DOI: 10.1038/sj.leu.2401891
|View full text |Cite
|
Sign up to set email alerts
|

Biological significance of the expression of HIV-related chemokine coreceptors (CCR5 and CXCR4) and their ligands by human hematopoietic cell lines

Abstract: The aim of this study was to learn more about the role of the HIV-related chemokine-chemokine receptor axes in human hematopoiesis. To address this issue we phenotyped 35 selected hematopoietic cell lines for the expression of CD4, CXCR4 and CCR5. We next evaluated the functionality of these chemokine receptors by calcium flux and chemotaxis assays, and by the ability of SDF-1, MIP-1␣, MIP-1␤ and RANTES to influence the growth of the cells expressing CXCR4 and/or CCR5. Lastly, we examined whether human hematop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 45 publications
5
31
0
Order By: Relevance
“…Generally, the biologic effects of SDF-1 on RMS cells observed here are consistent with those reported by us and others for human hematopoietic cells [6][7][8]22,23 and involve primarily cell interactions with the microenvironment and their migration rather than cell proliferation and/or survival. [6][7][8][9]22,23 However, the possibility that SDF-1 influences the metastatic potential of RMS in synergy/ cooperation with other factors cannot be excluded.…”
Section: Cxcr4-sdf-1 Axis In Rhabdomyosarcomas 2603supporting
confidence: 91%
See 1 more Smart Citation
“…Generally, the biologic effects of SDF-1 on RMS cells observed here are consistent with those reported by us and others for human hematopoietic cells [6][7][8]22,23 and involve primarily cell interactions with the microenvironment and their migration rather than cell proliferation and/or survival. [6][7][8][9]22,23 However, the possibility that SDF-1 influences the metastatic potential of RMS in synergy/ cooperation with other factors cannot be excluded.…”
Section: Cxcr4-sdf-1 Axis In Rhabdomyosarcomas 2603supporting
confidence: 91%
“…22 The CXCR4 antigen was detected with phycoerythrin (PE)-anti-CXCR4 monoclonal antibody (MoAb; R&D Systems, Minneapolis, MN), clone no. 12.G5.…”
Section: Facs Analysismentioning
confidence: 99%
“…Based on these and our other observations [11,12,19,38], we conclude that SDF-1 is an important factor regulating the interaction of lymphohematopoietic cells with the microenvironment but is not primarily involved in regulating proliferation or survival of these cells.…”
Section: Ccr5supporting
confidence: 72%
“…Previously we reported that several human hematopoietic cell lines expressed the HIV-related chemokine receptors CXCR4 and CCR5 [19]. In our current study, we selected 26 human CXCR4 (Tables 1-3).…”
Section: Stimulation Of Cxcr4 + Cell Lines By Sdf-1 Results In Phosphmentioning
confidence: 99%
“…25,56,66 On certain myeloid progenitor cell lines, a suppressive effect of SDF-1 was reported, 67 although this was not the case for others, in spite of expression of functional CXCR4. 68 In combination with other cytokines, SDF-1 was actually found to promote the proliferation of human CD34 ϩ cells purified from normal adult peripheral blood although when SDF-1 was added alone, only survival was supported, not mitogenesis. 69 These findings highlight the role other factors can have in influencing the effects chemokines exert on hematopoietic cell proliferation control as well as the importance of the progenitor subset investigated, as is also indicated by earlier evidence of opposing actions of MIP-1␣ (and TGF-␤) in stimulating the proliferation of later progenitor types but inhibiting their more primitive precursors.…”
Section: Org Frommentioning
confidence: 99%